Impacts of Adaptive Reuse of Heritage Buildings to Small Hotel Buildings in Bangkok - Chotewit Pongsermpol; Prapatpong Upala (My University, 2017)
Adaptive reuse (AR) is the process of reusing building to new purposes. In Bangkok, the popularity of AR turned to small hotels (AR-hotel) is increasing. There are more criteria for substantial renovation, business investment and valuing of heritage buildings but no concern to the community surrounding. This study was aimed to investigate community impacts occurred from AR-hotel projects. The key variables focused on four main issues - physical, economic, value and social issues. The results indicated that there were better physical improvements, livable area, more public social interaction whereas there was a little disturbance, and not much socialization of privacy. Keywords: adaptive reuse; hotel; heritage building; community impacts;ISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Adaptive Reuse; Popularity; Cultural Heritage Management and Preservation